PERANAN KELOMPOK TANI TERHADAP KEBERHASILAN PENYALURAN PUPUK BERSUBSIDI DI DESA KLAMPOK KECAMATAN SINGOSARI KABUPATEN MALANG - Endi, Endi; Asnah, Asnah; Mutiara, Farah (Universitas Tribhuwana Tunggadewi, 2024)
This research aimed to determine the role of farmer groups in the successful distribution of subsidized fertilizers. This study uses a descriptive method approach and data collection techniques using interviews, documentation, and observation. The result shows the role of farmer groups in distributing subsidized fertilizers in Klampok Village, Singosari District with the following percentages: meetings between farmer groups 84%, visits to the Ministry of Industry and Trade 100%, farmer group knowledge about fertilizers subsidized 100%, discussions about subsidized fertilizers 69%, information about subsidized fertilizers 79%, participation of farmer groups by attending meetings with the Ministry of Industry and Trade 85%, implementation of subsidized fertilizer distribution programs 99%, meaning that the role of farmer groups in the distribution of subsidized fertilizers has been carried out successfully, such as extension workers helping and guiding farmers in preparing RDKK (Definitive Needs Group Plans)